Signal grass structure at different sites of the same pasture under three grazing intensities - doi: 10.4025/actascianimsci.v35i1.11801 (Acta Scientiarum. Animal Sciences, 2012)
The experiment was conducted to evaluate Brachiaria decumbens cv. Basilisk at different sites of the same pasture featuring varying grazing intensities (under grazed, properly grazed and overgrazed). The pasture was managed under continuous stocking using 200-kg cattle and grass height kept at about 25 cm. The randomized block design was used, with three replications. Sward height (38.0 cm) and extended plant height (85.2 cm) were greater at the under grazed site. The falling index was lower at the properly grazed site (1.28). At the under grazed site, the masses of green leaf blade (3442 kg ha-1 DM), green stem (8370 kg ha-1 DM), green forage (11812 kg ha-1 DM) and total forage (14137 kg ha-1 DM) were higher when compared to the overgrazed and properly grazed sites. Dead material mass was higher at the properly grazed (3422 kg ha-1 DM) and under grazed (2324 kg ha-1 DM) sites. At the under grazed sites, there was a higher occurrence of tillers taller than 40 cm. Tillers with sizes between 10 and 30 cm predominated in properly grazed sites. In overgrazed site there was a higher share of tillers with sizes smaller than 20 cm. There is spatial variability of vegetation in the same pasture of Brachiaria decumbens cv. Basilisk due to uneven grazing by cattle.